88. Increasing Bioburden of Candida auris Body Site Colonization is Associated with Environmental Contamination. (15th December 2022) - Sansom, Sarah; Gussin, Gabrielle M; Singh, Raveena D; Bell, Pamela B; Benson, Ellen C; Makhija, Jinal; Froilan, Mary Carl; Saavedra, Raheeb; Pedroza, Robert; Thotapalli, Lahari; Fukuda, Christine; Gough, Ellen; et al.
Abstract: Background: Environmental contamination is suspected to play a key role in transmission of Candida auris in healthcare facilities. We recently showed that environmental surfaces near C. auris -colonized patients are commonly recontaminated within hours after disinfection. Clinical factors contributing to environmental contamination are not well characterized. Methods: We conducted a multi-regional (Chicago, IL; Irvine, CA) prospective study of environmental contamination associated with C. auris colonization at six long-term care facilities (LTCF) and 1 acute-care hospital (ACH). On day of sampling, 5 participant body sites were cultured once, followed by routine daily room cleaning by facility staff, then targeted disinfection of high-touch surfaces with hydrogen peroxide wipes by research staff. Surfaces were cultured for C. auris using pre-moistened sponge-sticks and neutralizer immediately pre- and post-disinfection, and 4, 8, and 12 hours post-disinfection. We calculated the odds of surface recontamination after disinfection as a function of body site colonization with C. auris using generalized estimating equations to account for clustering among multiple surfaces within timepoints, patients, and facilities. Models included an interaction between facility type and colonization. Results: C. auris was cultured from ≥1 body site in 41 participants (12 ACH and 29 LTCF patients, 205 body sites) on day of sampling. Proportion of body sites colonized did not vary by facility type (Table ). Although environmental contamination rates were similar prior to disinfection [ACH 38% (n=60 samples) vs LTCF 29%, (n=145 samples), p=0.209)], the proportion of surfaces recontaminated between 4–12 hours after disinfection was higher in ACH vs LTCF (n=574 samples) (Figure ). Number of body sites colonized with C. auris was associated with higher odds of environmental recontamination [ACH: OR 2.16 (95% CI 1.63–2.88), p< 0.001; LTCF: OR 1.40 (95% CI 1.07–1.84), p=0.015; Interaction ACH vs LTCF p< 0.001]. Figure. Percent of Environmental Surfaces Recontaminated with C. auris within 12 hours of Cleaning by Facility Type Conclusion: The number of body sites colonized was associated with odds of C. auris environmental contamination. Differences in environmental recontamination by facility type may be related to greater provider-patient interactions in ACH as a driving factor. Disclosures: Gabrielle M. Gussin, MS, Medline: Conducted studies in which hospitals and nursing homes received contributed antiseptic and/or environmental cleaning products|Stryker: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic products|Xttrium Laboratories: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic products Raveena D. Singh, MA, Medline: Conducted studies in which hospitals and nursing homes received contributed antiseptic and/or environmental cleaning products|Stryker: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic products|Xttrium Laboratories: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic products Raheeb Saavedra, AS, Medline: Conducted studies in which hospitals and nursing homes received contributed antiseptic and/or environmental cleaning products|Stryker: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic products|Xttrium Laboratories: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic products Nicholas M. Moore, PhD, D(ABMM), Abbott Molecular: Grant/Research Support|Cepheid: Grant/Research Support Susan S. Huang, MD, MPH, Medline: Conducted studies in which hospitals and nursing homes received contributed antiseptic and/or environmental cleaning products|Molnlyke: Conducted clinical studies in which hospitals received contributed antiseptic product|Stryker: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic products|Xttrium Laboratories: Conducted clinical studies in which hospitals and nursing homes received contributed antiseptic product Mary K. Hayden, MD, Sanofi: Member, clinical adjudication panel for an investigational SARS-CoV-2 vaccine.